Contractual Ethics Analysis of the Phenomenon of non-Transactional Consumption in Cafes: The Perspective of Islamic Economic and Justice - Asharsyira, Almeyda; Andriansyah, Yuli; Martins, José Moleiro (Tasharruf: Journal Economics and Business of Islam, 2026)
This study examines the increasingly common phenomenon of non-transactional consumption in cafes, known locally as "rojali" (rarely buying groups), where customers utilize amenities such as seating and Wi-Fi without purchasing products. The focus of this study is to evaluate the ethical and contractual implications of this behavior through the lens of Islamic economics, positioning this phenomenon as a consumption ethics issue that impacts the sustainability of micro-enterprises. The study uses a qualitative-descriptive approach with the method narrative review and conceptual-normative analysis of scientific literature, media reports, and the latest industry data for 2025. The results of the analysis show that the practice of "rojali" reflects a non-conformity with the principles of contract implicit and fairness values ('adl), because there is utilization of facilities without a clear agreement and appropriate compensation. This action is categorized as a form of taking advantage without rights (akhdz bi ghairi haqq) which results in injustice (oppression) for business owners, with a real impact of up to a 60% decrease in daily income. As a solution, this study recommends a strategy based on Islamic economic ethics through affirmation contract implicit in operational policies and strengthening of muamalah literacy to build consumer awareness of moral responsibility. This approach is expected to maintain a balance between the cafe's function as an inclusive social space and the protection of assets (hifz al-mal) and business sustainability.